On how much biodiversity is covered in Europe by national protected areas and by the Natura 2000 network: insights from terrestrial vertebrates. Issue 4 (21st May 2015) - Maiorano, L.; Amori, G.; Montemaggiori, A.; Rondinini, C.; Santini, L.; Saura, S.; Boitani, L.
Abstract: The European Union has made extensive biodiversity conservation efforts with the Habitats and Birds Directives and with the establishment of the Natura 2000 network of protected areas, one of the largest networks of conservation areas worldwide. We performed a gap analysis of the entire Natura 2000 system plus national protected areas and all terrestrial vertebrates (freshwater fish excluded). We also evaluated the level of connectivity of both systems, providing therefore a first estimate of the functionality of the Natura 2000 system as an effective network of protected areas. Together national protected areas and the Natura 2000 network covered more than one‐third of the European Union. National protected areas did not offer protection to 13 total gap species (i.e., species not covered by any protected area) or to almost 300 partial gap species (i.e., species whose representation target is not met). Together the Natura 2000 network and national protected areas left 1 total gap species and 121 partial gap species unprotected. The terrestrial vertebrates listed in the Habitats and Birds Directives were relatively well covered (especially birds), and overall connectivity was improved considerably by Natura 2000 sites that act as stepping stones between national protected areas. Overall, we found that the Natura 2000 network represents at continental level an important network of protected areas that acts as a good complement to existing national protected areas. However, a number of problems remain that are mainly linked to the criteria used to list the species in the Habitats and Birds Directives. The European Commission initiated in 2014 a process aimed at assessing the importance of the Birds and Habitats Directives for biodiversity conservation. Our results contribute to this assessment and suggest the system is largely effective for terrestrial vertebrates but would benefit from further updating of the species lists and field management. Abstract : Cuánta Biodiversidad Europea es Tomada en Cuenta por las Áreas Protegidas Nacionales y cuánta por la Red Natura 2000: Percepciones de los Vertebrados Terrestres Resumen: La Unión Europea ha hecho esfuerzos extensos de conservación de la biodiversidad con las Directivas de Hábitat y de Aves y con la creación de la red de áreas protegidas Natura 2000, una de las redes más grandes de áreas de conservación a nivel mundial. Realizamos un análisis de falta de datos en todo el sistema Natura 2000 más las áreas protegidas nacionales y todos los vertebrados terrestres (excluimos a los peces de agua dulce). También evaluamos el nivel de conectividad de ambos sistemas, proporcionando así un primer estimado de la funcionalidad del sistema Natura 2000 como una red efectiva de áreas protegidas. La red Natura 2000, junto con las áreas protegidas nacionales, cubrió más de un tercio de la Unión Europea. Las áreas protegidas nacionales no ofrecieron protección para un total de 13 especies del vacío (es decir, las especies que no abarcaron ninguna área protegida) o para casi 300 especies parciales del vacío (es decir, especies cuyo objetivo de representación no es alcanzado). La red Natura 2000, junto con las áreas protegidas nacionales, dejó un total de una especie del vacío y 121 especies parciales del vacío sin protección. Los vertebrados terrestres enlistados en las Directivas de Hábitat y de Aves fueron tomados en cuenta relativamente bien (especialmente las aves), y la conectividad general mejoró considerablemente por los sitios Natura 2000, los cuales funcionan como peldaño entre las áreas protegidas nacionales. En general, encontramos que la red Natura 2000 es, a nivel continental, una red importante de áreas protegidas que actúa como un buen complemento para las áreas protegidas nacionales existentes. Sin embargo, todavía permanece un número de problemas que están conectados principalmente con la lista de especies en las Directivas de Hábitat y de Aves. La Comisión Europea inició en 2014 un proceso enfocado a la importancia de estas directivas para la conservación de la biodiversidad. Nuestros resultados contribuyen a esta evaluación y sugieren que el sistema es generalmente efectivo para los vertebrados terrestres pero que se beneficiaría de una mayor actualización de las listas de especies y del manejo en el campo.